Mobile Real Estate: Legal Status and Succession Principles - KIRILLOVA, Elena Anatolyevna; SUSLIKOV, Vladimir Nikolaevich; BOGDAN, Varvara Vladimirovna; BAYBARIN, Andrey Andreevich; SHEVELEVA, Svetlana Viktorovna (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The subject of research in this article is mobile real estate as an object of civil rights, the actuality of research topic is predetermined by a wide range of legal regulation issues in connection with title relations in real estate sphere, demand intensity on mobile real estate and economic significance of real estate in commercial turnover of all countries. Currently, neither theory nor legal practice solved a number of issues related to legal status of mobile real estate. The purpose of this research is to determine the legal regime of mobile real estate and try to fill the gap in that area of civil law science. On the basis of this research, the core conclusion was made: mobile real estate should be determined as movable property with specific features including loose relation to land, unnecessary state registration, single component, unnecessary land title ownership. Mobile real estate should be inherited taking into account those specific features.
Keywords: housing sector, real estate, movable property, mobile real estate, succession